Efficacy and Safety of Single-dose Fosfomycin for Uncomplicated Urinary Tract Infection in Women: Systematic Review and Meta-analysis - Tania Verma; Gaurav Singh Manhas; Rameshwar Singh Manhas (Journal of Mid-Life Health, 2025)
In this meta-analysis and systematic review, the effectiveness and safety of single-dose fosfomycin were evaluated in comparison to other antibiotics for treating uncomplicated urinary tract infections (UTIs) in women, including asymptomatic bacteriuria (ASB) in pregnant women. Two independent reviewers conducted an electronic search on until December 2023 to search for randomized controlled trials that studied the efficacy and safety of fosfomycin for management of uncomplicated UTI in women or ASB in pregnant women and included those that fulfilled the eligibility criteria. The results showed that single-dose fosfomycin was comparable with other antibiotic agents in clinical resolution of uncomplicated UTI (odds ratio [OR]: 1.11, 95% confidence interval [CI] 0.88–1.41, I2 = 0%, P = 0.37, moderate certainty). Moreover, single-dose fosfomycin was equal to other antibiotics in the microbiological resolution of uncomplicated UTI (OR: 1.02, 95% CI: 0.83–1.25, I2 = 34%, P = 0.88, moderate certainty) and ASB among nonpregnant women (OR: 0.76, 95% CI: 0.45–1.28, I2 = 0%, P = 0.30, moderate certainty). The incidence of adverse events too was similar in patients receiving fosfomycin or other antibiotics (OR: 0.97, 95% CI: 0.77–1.23, I2 = 41%, P = 0.82, moderate certainty). Administering a single dose of fosfomycin is just as safe and effective as other antibiotics in treating uncomplicated UTIs in women. Prescribing a single dose of fosfomycin (3 g) as a regular practice may result in higher compliance rates and a reduced likelihood of antibiotic resistance.